A Comparison of the Unconventional Monetary Policies of the ECB and the FED - Bohůnek, Matěj (2016)
The monetary policy of the Fed and the ECB has greatly change as a result of the global crisis. The goal of the thesis is to analyse the evolution of unconventional monetary instruments in the USA and the EU after the outbreak of the global crisis and nowadays with the help of pivotal economic models; namely, the IS-LM-BP model and the quantity theory of money. In addition, the paper should assess the impacts of adopted instruments and programs and draw conclusions about their success. The theoretical part explains the IS-LM-BP framework and the quantity theory of money and describes the unconventional monetary tools that the central banks can use when the interest rates reach the zero lower bound. The practical part analyses EU and US economy with the explained models. Furthermore, the implemented instruments of the Fed and the ECB are described and compared. The thesis should be concluded with the claim that the transmission mechanism was restored with the help of the non-standard measures, however, the desirable price level stabilization has not been reached.